If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9=-(1+8x)-2(4-4x)
We simplify the equation to the form, which is simple to understand
-9=-(1+8x)-2(4-4x)
Remove unnecessary parentheses
-9=-1-8x-2*(4-4x)
Reorder the terms in parentheses
-9=-1-8x+(-8+8x)
Remove unnecessary parentheses
-9=-1-8x-8+8x
We move all terms containing x to the left and all other terms to the right.
+8x-8x=-1-8+9
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 7+x=.5(4*-2) | | 12x-4=5x-32 | | 3x+5+2x=54 | | 7x+20= | | 2x^2-17x+15=0 | | 5y+3=9y-1 | | 7+x=.5(4*2) | | 5x-1=3x+13 | | 5-4k=-(4k+1) | | 6x-12+3x+26=180 | | z^2(x+1)-3z(x+1)-70(x+1)=0 | | (1.1+k)5-7.6=1.6 | | d-4=-13 | | -2(w-7)+lOw=34 | | 7x+2y=7 | | 17+3(z+2)-11z=-7(z+2)+14 | | 20x+53= | | 2p-(1+8p)=4p-21 | | (15-y)+2=2y | | -2x+3=4x+75 | | Y+7-3=12 | | xz^2+z^2-3zx+4z-70x+70=0 | | 200-80=2l+80-80 | | 8r+7=49 | | s=p(1+rt) | | 14+s=-32 | | 4-3n=2n-36 | | -58+58=29p-14p | | 1x+5=3x-1 | | 4(x+5)=6x+4-2x+16 | | 9*0-7=-7 | | 7(m+7)=36-6m |